Etika raziskovanja v družbeni areni - Malnar, Brina (Družboslovne razprave, 2011)
The paper examines the key ethical dilemmas that may emerge between a researcher and society, mostly due to the collision of scientific, political and economic principles in the research environment. The starting point of the discussion is the role of the ĆtruthĆ as the main research principle, whose guiding role may become compromised due to research embeddedness in power relations. The article proceeds by exploring ways in which research practice and findings may become instrumentalised as a result of political, commercial or career-building pressures. It wraps up with the conclusion that socially responsible research ethics requires a reflective stance towards both personal research practice, as well as the public spin of research findings, and that the main societal-level ethical problem of contemporary sociological research is not so much the excessive politicisation of its findings, but that they lack a social impact.
Keywords: scientific method; Scientific research; Znanstveno raziskovanje; Society; Družba; Ethics; Etika; Politics; Politika